Kadazan dusun youth consumerist culture: social media, clothing and fashion - Andreas Totu; Romzi Ationg; Rose Patsy Tibok; Halina Sendera Mohd Yakin (Institute of Advanced Scientific Research, 2020)
Development at times brings to fore conflict between tradition and the need to modernise so as to keep abreast with current trends and approaches. In some rapid developing economies such as Malaysia, the populace is still generally conservative in terms of how they portray themselves particularly in style and fashion. Malaysians, particularly the older generation, are inclined to be selective and prefer fashion and attire forms that are modest and not exposing body shape or skin mainly due to religious and cultural norms and sensitivities. This traditional perspective is prevalent in Asian communities where preserving ‘face’ is paramount – so much so that members of that community would go to great lengths to avoid actions and behaviour that could be construed as ‘detrimental’ to dignity and self-worth. The fashion and attire choice of the younger generation often become issues of conflict between the young and their elders with the fashion sense of youths perceived to be dictated more by the fulfilment of social-media-induced wants rather than actual needs. This paper is an attempt to examine the fashion and attire choices of young Kadazan-Dusun milennials in Sabah, Malaysia. The study involved four Focus Group discussions with six participants in each group consisting undergraduates of a local university in Kota Kinabalu, Sabah, Malaysia. The findings showed that while the youths on the wholewere inclined towards following current fashion trends, they would only indulge in this fashion preference at the right place and time to blend in with their circle of ‘cool modern global citizens’. Some participants however, especially from the rural areas, demonstrated displeasure towards extreme and ‘inappropriate’ fashion and attire. The outcome of this study also indicated Instagram as contributory to the fashion and attire choices of Kadazan-Dusun youths.